The relative efficiency of alternative land tenure contracts in Arsi zone, Ethiopia - Gavian, S.; Ehui, Simeon K. (Agricultural Economics Society of Ethiopia, 1996)
This paper examines the relative efficiency of alternative land tenure arrangements using a single region (Arsi) in Ethiopia as a case study. The first part of the paper discusses land tenure issues in sub-Saharan Africa. The second part outlines the conceptual framework. Interspatial and intertemporal total factor productivity measures are presented under this section. The third section describes the study area and data collection. Topics covered under this section include the study area, description of land contracts in the survey region, defining security, and transforming the production data. The last section highlights productivity estimates.